A Multidisciplinary-economic Framework of Analysis - Piet K. Keizer (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2015)
Human motivation offers energy, and circumstances offer possibilities. Only in combination does human motivation and circumstance yield action. Over time, desires and opportunities to satisfy them closely interact with one another. Orthodox economics analyzes economic motivation in interaction with scarce natural resources. It assumes that perfect rationality and non-sociality create a so-called economic world and analyzes the economic mechanism of allocation of scarce resources. Neoclassical economists use this world as a theoretical foundation for their empirical research. Heterodox economics rejects this strategy of isolating one motivation, a strategy that ignores the psychic and the social problem. However, the heterodox idea of human motivation, being variable and endogenous, is badly analyzed. This leads the author to construct a psychic and a social world that is completely comparable with the agent-structure model of the economic world. The three isolated worlds are integrated by analyzing the interactions between the three worlds. In the integrated world, the economic structure, the psychic structure and the social structure are one another's foundations. This human world gives familiar economic concepts such as utility, efficiency, rationality, price, value, cost and benefit a different meaning. Similarly, psychic concepts such as Self, willpower and personality and social concepts such as status, power, culture and morality are given different meanings. To make the model more realistic, it should be made dynamic and historical and be placed in the context of the world as an open system.
Keywords: 330; orthodox economics; neoclassical economics; rationality; morality; multidisciplinary economics; us versus them; cognitive closure